ChemInform Abstract: Rhodium‐ and Platinum‐Catalyzed [4 + 3] Cycloaddition with Concomitant Indole Annulation: Synthesis of Cyclohepta[b]indoles. Issue 30 (4th July 2013) - Shu, Dongxu; Song, Wangze; Li, Xiaoxun; Tang, Weiping
Abstract The procedure renders possible an access to various highly functionalized important structural motifs.